Introduction to qi gong [videorecording (DVD)] - Holden, Lee, 1969- (Holden Qi gong., 2017)
Described as the art of effortless power, Qi Gong is easy to follow and effective for improving your health. Combining gentle stretching, energy-activating exercise, simple movements for strength, and flowing movements, Qi Gong gives a complete body/mind workout.